Religious education teachers’ perspectives on character education - Metcalfe, Jason (British Journal of religious education, 2021)
This article presents the findings of a qualitative interview study undertaken with RE teachers (n = 30), working in English schools with secondary status. Despite recent policy interest in character education, there is a lacuna of information about the extent RE contributes to character education. The present study focuses on teachers’ perspectives on virtue literacy, a theme identified across participants in response to open-ended prompts about RE, religion and character. The participants in the sample hold different worldviews and work across a range of schools, providing a variety of informative perspectives. There were clear differences between the responses of participants’ from faith and non-faith schools regarding the contribution of RE to pupils’ virtue literacy. These findings mark a distinctive contribution to our understanding of the differences between RE in faith and non-faith schools.